2018
DOI: 10.1016/bs.mie.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally Gated Electron Transfer in Nitrogenase. Isolation, Purification, and Characterization of Nitrogenase From Gluconacetobacter diazotrophicus

Abstract: Nitrogenase is a complex, bacterial enzyme that catalyzes the ATP-dependent reduction of dinitrogen (N) to ammonia (NH). In its most prevalent form, it consists of two proteins, the catalytic molybdenum-iron protein (MoFeP) and its specific reductase, the iron protein (FeP). A defining feature of nitrogenase is that electron and proton transfer processes linked to substrate reduction are synchronized by conformational changes driven by ATP-dependent FeP-MoFeP interactions. Yet, despite extensive crystallograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…We chose to study CowN in the diazotroph Gluconacetobacter diazotrophicus , an agriculturally relevant organism with a well-characterized nitrogenase ( 30 , 31 , 32 ). Importantly, G. diazotrophicus has no alternative nitrogenases so any regulatory cross talk between nitrogenases that may influence CowN expression can be ruled out.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We chose to study CowN in the diazotroph Gluconacetobacter diazotrophicus , an agriculturally relevant organism with a well-characterized nitrogenase ( 30 , 31 , 32 ). Importantly, G. diazotrophicus has no alternative nitrogenases so any regulatory cross talk between nitrogenases that may influence CowN expression can be ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogenase was expressed and purified based on previously described methods ( Fig. S7 ) ( 30 ). Our typical maximum MoFeP C 2 H 2 reduction activity is about 1500 nmol mg −1 min −1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the Fe protein binds to nitrogenase via a positively charged docking site. [40][41][42] We hypothesized that TGA-CdS NPs with negative charges on their surface will bind to the docking site and force improved electron transfer process.…”
Section: Discussionmentioning
confidence: 99%